Narodne manjšine in Ustava - Škrk, Mirjam (Pravnik, 2024)
The Slovenian Constitution regulates both individual and collective rights of the autochthonous Italian and Hungarian national minorities and the status of Roma residing in Slovenia. It has faced criticism for not extending minority protection to Slovenian citizens who are part of nations and nationalities of the former Yugoslav republics, often referred to as “the new minorities”. Besides, Austrian authorities have persistently urged Slovenia to grant constitutional minority rights to individuals belonging to the German-speaking ethic group in Slovenia. In the light of the critical remarks the Advisory Committee on the Framework Convention for the Protection of National Minorities adopted in its Fifth Opinion on Slovenia, the article examines the protection of national minorities in international law. The author observes that the current regulation of national minorities in the Constitution is in conformity with international legal requirements for minority protection. Moreover, the Advisory Committee on the Framework Convention for the Protection of National Minorities acted ultra vires by calling on Slovenia to consider extending constitutionally protected minority rights to the German-speaking ethnic group and the new minorities. Nonetheless, the claims of constitutional minority protection made by the new minorities are legitimate. It is within the competence of the National Assembly to consider these claims.
Keywords: individual and collective minority rights; individualne in kolektivne manjšinske pravice; narodne manjšine; narodne manjšine in mednarodno pravo; national minorities and international law; pristojnost nadzornih teles za narodne manjšine in notranje pravo držav pogodbenic; regional and special treaties on the protection of minorities; regionalne in posebne pogodbe o varstvu narodnih manjšin; the competence of the supervisory bodies on national minorities and the internal law of the contracting parties; the Constitution; Ustava